Implementasi Pengetahuan, Persepsi, Dan Penerapan Kesehatan Dan Keselamatan Kerja (K3) Pada Pembelajaran Praktik Program Keahlian Teknik Pemesinan Dan Teknik Ototronik Di SMK Negeri 2 Karanganyar - Tomy Adam; Husin Bugis; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Abstract               This study aims to determine the level of knowledge, perception, and application of Occupational Health  and Safety(OHS) in class XII students of the Mechanical Engineering and Autotronic Engineering expertise program. This research used descriptive quantitative research methods. Retrieval of data using test instruments and questionnaires. The population of this study was 135 students of class XII,  67 students of mechanical engineering and 68 students of autotronic engineering.              The results showed that the level of OHS knowledge of class XII students of Mechanical Engineering, 76.12%, was in the good category, 19.40% was good enough and was 4.48% not good enough. Meanwhile, in class XII,  Autotronic Engineering which was included in the good category was 75%, 17.65% was good enough, and 7.35% was not good. The highest average gain lies in the OHS Terms and Principles indicator, namely for the engineering department, 98.51% of students are in the good category and 98.53% for the auto-electronics department, 98.53% of the students are in the good category.For the level of student perception, in class XII Mechanical Engineering which is in the good category is 95.52%, 4.48% is quite good, and there are no students in the poor category. Meanwhile, the level of students' perceptions in class XII of Autotronic Engineering  which was in the good category was 98.51%, 2.99% was quite good, and no student was in the poor category. The highest average gain lies in the OHS Terms and Principles indicator, namely for the engineering department, 98.51% of students are in the good category and 98.53% for the auto-electronics department, 98.53% of the students are in the good category.For the level of application, the highest percentage of students in mechanical engineering always did 72.14%, sometimes 26.37% and students did not do 1.49%. Meanwhile, there were 70.59% of students in autotronic engineering who always did it, 27.94% of the students did sometimes, and 1.47% did not. The highest average gain lies in the indicators of cleanliness and health of the work environment where for the engineering department, 72.14% of students always apply OHS measures. Meanwhile, for the autronic department, 70.59% of students always apply OHS actions.